2014
DOI: 10.1051/0004-6361/201321299
|View full text |Cite
|
Sign up to set email alerts
|

Planckintermediate results

Abstract: Using Planck data combined with the Meta Catalogue of X-ray detected Clusters of galaxies (MCXC), we address the study of peculiar motions by searching for evidence of the kinetic Sunyaev-Zeldovich effect (kSZ). By implementing various filters designed to extract the kSZ generated at the positions of the clusters, we obtain consistent constraints on the radial peculiar velocity average, root mean square (rms), and local bulk flow amplitude at different depths. For the whole cluster sample of average redshift 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(9 citation statements)
references
References 132 publications
(135 reference statements)
1
8
0
Order By: Relevance
“…äb −ba (8) it must represent, to some extent, a type of monopole of "Coulomb" (for further details see [38]). It should be noted that the symmetry (1) allows several solutions both type O as well as D of Petrov, for example, similarly to the symmetry of Bianchi-I with g 00 = 1.…”
Section: The Interval Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…äb −ba (8) it must represent, to some extent, a type of monopole of "Coulomb" (for further details see [38]). It should be noted that the symmetry (1) allows several solutions both type O as well as D of Petrov, for example, similarly to the symmetry of Bianchi-I with g 00 = 1.…”
Section: The Interval Metricmentioning
confidence: 99%
“…This discovery is confirmed on other works related to the direction of the polarization of Quasars [2] and the rotation of spiral galaxies [3]. Other important discoveries, though exposed to criticisms and refutation, are the ones obtained with the data of the satellites WMAP and Planck: the non-Gaussianity in the CMB (see examples [4], [5]), vast empty spaces [6],large-scale peculiar velocities larger than the expected on the standard cosmological model (Dark Flow anomaly) [7], [8], adverse data analysis of gravitational waves for some cosmological models of inflation and string theory [9] and inside the LCDM cosmological model, discrepancies with a few observations; such as the measurement of the current rate of expansion H 0 , the galaxies shear power spectrum and the number of galaxy clusters, as a result of the Plank satellite's rates measurements [10], and to a lesser extent a deficit of 5 − 10% at the low power spectrum mode [l < 40] vs. the standard model LCDM [11] , the lack of evidence of dynamic dark energy [12], the reduction of the possible standard cosmological model, such as exponential potential model, simple hybrid inflation models, and monomial potential models of degree n > 2 [13]. Moreover, and this being another restrictions to models with variable physical constants, both temporal and special, it was found that the time variable independent of the fine-structure constant α and the mass of the electron m e are limited by the data of the Plank satellite for ∆α/α = (3.6 ± 3.7) • 10 −3 and ∆m e /m e = (4 ± 11) • 10 −3 at a 68% level of confidence and for a spatial variation of the fine-structure constant α, at ∆α/α = (−2.4 ± 3.7) • 10 −2 [14]; related to the same topic and base on the data of VLT/UVES and the Keck telescope, it has been observed a dipole of the ∆α/α variation with a amplitude of 0.97 +0.22 −0.20 • 10 −5 [15] this implying an anisotropic variation of the α constant.…”
Section: Introductionmentioning
confidence: 99%
“…They include the alignment of quadrupole, octupole and ecliptic plane, a dipole anomaly in the power spectrum that breaks statistical isotropy and the hemispherical anomaly whose maximum asymmetry is observed in the ecliptic frame. On the other hand, large scale bulk flows have also been detected with an amplitude which has been claimed to exceed the predictions of standard ΛCDM [8][9][10]. Although the statistical significance of such anomalies is * Electronic address: migueapa@ucm.es † Electronic address: maroto@ucm.es somewhat limited, they have motivated the search for preferred directions in cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, we use three CMB datasets that combine ACT and Planck data. The first dataset is a componentseparated internal linear combination map (ILC) [30], referred to as DR4 ILC, which uses night-time ACT observations from DR4, principally from 2014 to 2015 [32,33] as well as Planck data in eight bands, from 30 to 545 GHz, from the PR2 (2015) release [34]. The map is created by minimizing the variance and is dominated by CMB and kSZ signals but also has other foregrounds including thermal SZ and cosmic infrared background (CIB) contributions.…”
Section: A Act Datamentioning
confidence: 99%